2006
DOI: 10.1542/peds.2006-0590
|View full text |Cite
|
Sign up to set email alerts
|

Premedication for Nonemergent Neonatal Intubations: A Randomized, Controlled Trial Comparing Atropine and Fentanyl to Atropine, Fentanyl, and Mivacurium

Abstract: OBJECTIVE. The purpose of this work was to investigate whether using a muscle relaxant would improve intubation conditions in infants, thereby decreasing the incidence and duration of hypoxia and time and number of attempts needed to successfully complete the intubation procedure. PATIENTS/METHODS. This was a prospective, randomized, controlled, 2-center trial. Infants requiring nonemergent intubation were randomly assigned to receive atropine and fentanyl or atropine, fentanyl, and mivacurium b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
104
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 26 publications
9
104
1
2
Order By: Relevance
“…Using the rocuronium dose of 0.5 mg kg À1 in our study, we found the duration of rocuronium to be much shorter (judged by gross motor movements); this difference is likely due to prolongation of duration of rocuronium by inhaled anesthetic agents in the aforementioned studies. 13 Prospective studies by Roberts et al 10 and Dempsey et al 11 showed successful facilitation of endotracheal intubation in neonatal populations similar to ours using mivacurium. Roberts et al 10 showed higher success rates for intubations by the second attempt, shorter duration of intubation procedure and decreased periods of desaturations.…”
Section: Drug Of Choicesupporting
confidence: 74%
See 4 more Smart Citations
“…Using the rocuronium dose of 0.5 mg kg À1 in our study, we found the duration of rocuronium to be much shorter (judged by gross motor movements); this difference is likely due to prolongation of duration of rocuronium by inhaled anesthetic agents in the aforementioned studies. 13 Prospective studies by Roberts et al 10 and Dempsey et al 11 showed successful facilitation of endotracheal intubation in neonatal populations similar to ours using mivacurium. Roberts et al 10 showed higher success rates for intubations by the second attempt, shorter duration of intubation procedure and decreased periods of desaturations.…”
Section: Drug Of Choicesupporting
confidence: 74%
“…[23][24][25] In addition to improving chances for successful intubation, paralytic agents are reported to attenuate adverse physiologic changes experienced during intubation attempts. Increased intracranial pressure, 2,3,26,27 increased systolic blood pressure 28 and longer duration of hypoxemia 10,29 have been reported in awake vs paralyzed neonatal intubations. The longterm consequences of these physiologic changes are not known.…”
Section: Common Practicesmentioning
confidence: 94%
See 3 more Smart Citations